Factors Influencing Obesity: A Systematic Literatur Review - Bayu Tri Utami; Iis Rahmawati; Tantut Susanto (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2026)
Adolescent obesity represents a significant global health issue escalating in both developed and developing countries, including Indonesia, with impacts on non-communicable disease risks and psychosocial disorders. The complexity of its causes requires a holistic approach via the Socio-Ecological Model (SEM), integrating individual, social, environmental, and policy factors. This study aims to identify and analyze these factors influencing adolescent obesity incidence. A Systematic Literature Review (SLR) method guided by PRISMA 2020 was employed, searching PubMed, Scopus, ScienceDirect, and Google Scholar (2020–2024) using keywords on adolescent obesity, socio-ecological model, and risk factors. From 2,530,000 initial articles, screening of titles, abstracts, and full texts yielded 12 high-quality articles for synthesis. Synthesis revealed individual-level factors such as high-calorie low-fiber diets, low physical activity, sedentary behavior, academic stress, and poor self-regulation contribute to elevated BMI in adolescents. Social factors include family parenting styles, peer influence, and social media; environmental aspects encompass limited healthy food access, fast food dominance, and scarce sports facilities; policy measures like unhealthy food marketing regulations and sugary drink taxes remain suboptimal in developing countries. In conclusion, adolescent obesity arises from multidimensional SEM interactions, necessitating comprehensive multilevel prevention interventions involving families, schools, communities, and government policies for sustained effectiveness.